The UCP 600 Rules In Letter Of Credit (LC): Selected Issues (UUM Journal of Legal Studies, 2016)
The Uniform Customs and Practice (UCP) is the primary source for letter of credit (LC) transaction. Prior to the publication of the UCP, the rules in LC originating from trade customs and practices were not unanimously applied by traders. The International Chamber of Commerce (ICC) whose function is to harmonize the various trade customs practiced in  LC, had initiated to compile those rules and published them under one specific reference and named it as the UCP. The UCP is always been updated in order to serve current market needs in regards to LC issues.  Thus far, there is no specific statute regulated for LC. The UCP, though customary in nature and has no legal effect, has been adopted by more than 175 countries. Currently, it is unlikely to find the LC transactions, which is not governed by the UCP. Compared to the previous versions, the latest version of the UCP 600 is claimed to be comprehensive and offers modification to the preceding LC rules.  This paper discusses the rules provided by the latest UCP 600 focusing on the significant issues in LC such as bankersâ€™ autonomy, revocable and irrevocable LC, strict compliance, notice of refusal and fraud. Comparisons are scrutinized with the previous versions of the UCP and reviews are highlighted wherever necessary. In addition, reference is sought to case-law to illustrate certain issues. Furthermore, this paper examines the improvements contributed by these latest rules. Last but not least, it seeks to submit proposals for future improvement of the current UCP 600.Keywords: UCP 600; Letter of Credit; autonomy; strict compliance; notice of refusal, fraud.